Crosstalk Between Plasma Cytokines, Inflammation, and Liver Damage as a New Strategy to Monitoring NAFLD Progression - Fontes-Cal, Tereza C. M.; Mattos, Rafael T.; Medeiros, Nayara I.; Pinto, Bruna F.; Belchior-Bezerra, Mayara; Roque-Souza, Bruna; Dutra, Walderez O.; Ferrari, Teresa C. A.; Vidigal, Paula V. T.; Faria, Luciana C.; Couto, Cláudia A.; Gomes, Juliana A. S. (Frontiers in Immunology, 2021)
Cytokines are involved in the immunopathogenesis of nonalcoholic fatty liver disease (NAFLD), but the relationship between them and clinical parameters of NAFLD progression is still unknown. Using flow cytometry, we evaluated the plasma levels of IL-1beta, IL-6, IL-12, TNF and IL-10 and their association with clinical and biochemical parameters of liver function during simple steatosis (NAFL) and nonalcoholic steatohepatitis (NASH) in biopsy-proven patients. The NASH patients showed higher levels of IL-6 associated with a lower IL-10/IL-6 ratio. Besides heatmaps were similar in the NAFL and NASH groups, the same did not occur in signature curves, the NASH patients were high producers to IL-12 and IL-6 while the NAFL patients were not high producers of any cytokines evaluated. Integrative biomarker network analysis revealed that cytokines are differently correlated with clinical parameters, while IL-12, IL-10 presented moderate and negative correlations with glycemic and lipid profile in the NAFL group. The NASH group IL-12 and TNF revealed stronger and positive correlations with transient elastography parameters and NAFLD liver fibrosis score. These data suggest that IL-6 and IL-10 might act in chronic inflammation and insulin resistance whereas IL-12 and TNF may be involved in promoting liver damage and NAFLD progression. Plasma concentration analysis of these molecules and their association with clinical parameters can be used as new biomarkers to monitoring NAFLD progression and to reflect NASH development.